Elevated serum homocysteine level as an independent risk factor for erectile dysfunction: a prospective pilot case–control study - Zhang, Z.; Xu, Z.; Dai, Y.; Chen, Y. (Andrologia, 2017)
Summary Homocysteine is an amino acid that is produced from the metabolic demethylation of dietary methionine. It has gained arising attention for its association with increased risk of myocardial infarction, stroke and venous thromboembolism. Erectile dysfunction (ED), especially for vasculogenic ED, is a vascular disorder of cavernosal vascular bed. In this prospective pilot case–control study, we investigated plasma homocysteine levels in 32 ED patients and 20 healthy control men. Related patients characteristics including age, weight, height, marital status, smoking and drinking status, level of education were collected and analysed as well as penile colour Doppler ultrasound parameters. ED patients were further categorised into mild, moderate and severe ED based on 5‐item of the International Index of Erectile Function. Higher homocysteine levels were observed in ED patients as compared with controls (p < .05). A multivariate logistic regression with likelihood ratio test revealed that homocysteine and penile peak systolic blood flow velocity (PSV) levels posed significant indicators for ED (chi‐square of likelihood ratio = 20.42, df = 2, p < .005) as well as moderate and severe ED occurrence (chi‐square of likelihood ratio = 28.50, df = 2, p < .005). The threshold value of homocysteine concentration to discriminate ED and control subjects was 12.65 μmol/L by performing receiver operating characteristic curve analyses. These data suggested that elevation of homocysteine levels was associated with an increased risk of ED.